Into the mainstream essays on Spanish American and Latino literature and culture - Febles, Jorge M., 1947- (Cambridge Scholars Press, 2006)
Into the Mainstream: Essays on Spanish American and Latino Literature and Culture is a direct outgrowth of Jorge Febles's involvement with the annual conference of the American Culture Association and the Popular Culture Association. In that sense, the compilation expands on a project initiated in 1993 by Helen Ryan-Ransom with her book Imagination, Emblems and Expressions: Essays on Latin American, Caribbean, and Continental Culture and Identity (Bowling Green, Ohio: Bowling Green State Un ...
Keywords: American literature -- Hispanic American authors -- History and criticism.; Hispanic Americans in literature.; Littérature américaine -- Auteurs américains d'origine latino-américaine -- Histoire et critique.; Américains d'origine latino-américaine dans la littérature.; Literary studies: general.; Cultural studies.; LITERARY CRITICISM -- European -- Spanish & Portuguese.; American literature -- Hispanic American authors; Hispanic Americans in literature; Criticism, interpretation, etc.